Adult-Onset Spinal Muscular Atrophy due to Mutations in the VRK1 Gene. (August 2021) - Sung, Angela; Moretti, Paolo; Shaibani, Aziz
Abstract : Objective: To expand our knowledge of the range of clinical phenotypes associated with vaccinia-related kinase 1 ( VRK1 ) gene mutations. Methods: We present clinical and molecular data of 2 individuals with slowly progressive weakness and a clinical syndrome consistent with adult-onset spinal muscular atrophy without pontocerebellar atrophy. Results: Genetic testing revealed likely pathogenic variants in the VRK1 gene in both subjects. One individual carried homozygous p.R321C (c.961 C>T), likely pathogenic variants. The other carried compound heterozygous p.V236M (c.706 G>A) and p.R321C (c.961 C>T), likely pathogenic variants. Notably, both patients were of Hispanic descent. Conclusions: We report 2 cases with VRK1 mutations presenting as adult-onset spinal muscular atrophy without pontocerebellar hypoplasia and review the current literature of similar cases. Our report expands the clinical spectrum of neurologic disorders associated with VRK1 mutations.